2000
DOI: 10.1046/j.1460-9568.2000.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographical projection from the superior colliculus to the nucleus of the brachium of the inferior colliculus in the ferret: convergence of visual and auditory information

Abstract: The normal maturation of the auditory space map in the deeper layers of the ferret superior colliculus (SC) depends on signals provided by the super®cial visual layers, but it is unknown where or how these signals in¯uence the developing auditory responses. Here we report that tracer injections in the super®cial layers label axons with en passant and terminal boutons, both in the deeper layers of the SC and in their primary source of auditory input, the nucleus of the brachium of the inferior colliculus (nBIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Visual or visual related (saccadic) information are reaching the different auditory relays such as the inferior colliculus and the MGB [125][127]. These visual activities can originate from direct retinal inputs [128], [129] or from projections from the upper layers of the superior colliculus [130] reaching the inferior colliculus. In some species (rodents and ferrets), the primary auditory cortex is receiving direct projections from visual areas [131], which is not the case in the cat and monkey (present study, [132].…”
Section: Discussionmentioning
confidence: 99%
“…Visual or visual related (saccadic) information are reaching the different auditory relays such as the inferior colliculus and the MGB [125][127]. These visual activities can originate from direct retinal inputs [128], [129] or from projections from the upper layers of the superior colliculus [130] reaching the inferior colliculus. In some species (rodents and ferrets), the primary auditory cortex is receiving direct projections from visual areas [131], which is not the case in the cat and monkey (present study, [132].…”
Section: Discussionmentioning
confidence: 99%
“…The superior colliculus in mammals possesses a topographic representation of both visual and auditory space, where frontal space overrepresentation has been observed in numerous species (Drager and Hubel, 1976; Doubell et al, 2000). The visual and somatosensory cortices also show overrepresentation of the foveal region (Yang et al, 1992; Kautz and Wagner, 1998; Zhang et al, 1999) and the face and hands (Penfield and Boldrey, 1937; Fujita and Konishi, 1991), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have found that the primate IC contains neurons with activity that depends on eye position (15)(16)(17), a signal that is necessary for compensating for the dissociations between visual and auditory spatial locations that occur naturally when the eyes move. There is also anatomical evidence for projections to the IC from the retina (18)(19)(20), visual cortex (21), and the SC (22,23 Gutfreund et al (14) in anesthetized owls suggests that visual inputs to the IC are prevalent, but normally silent.…”
mentioning
confidence: 99%